Peculiarities of cerebral hemodynamics and cerebral bioelectric activity under infectious mite borreliosis - O. V. Cherepova; S. V. Gusakova; M. V. Zlobina (Бюллетень сибирской медицины)
Cerebral hemodynamics state and peculiarities of bioelectric cerebral activity in patients with infectious mite borreliosis (IMB) have been investigated. 24 patients out of acute stage have been examined; the control group has been consisted of 10 healthy people. Values of rheographic index, index of vessel peripheral resistance, time of pulse wave spread, venous drainage index and elastic resistance index have been evaluated by rheoencephalography method (REG). ElectroEncephaloGram (EEG) has been registered in 12 abstractions according to the international system 10—20. Amplitude, frequency and indices of α-, β-, δ- and θ-rhythms, asymmetry degree and presence of paroxysmal activity have been evaluated. Use of EEG at patients with IMB has marked the α-rhythm suppression and increase of slow activity of δ- and θ-ranges, electric activity asymmetry and presence of paroxysmal discharges. By REG method there have been revealed expressed functional disturbances of cerebral circulation. Together with the impediment of venous drainage, this leads to the regulatory imbalance and the decrease of hemodynamic supply to separate cortex parts that may be a reason of bioelectric cerebral activity disturbances in patients with IMB.